2016
DOI: 10.1038/srep22745
|View full text |Cite
|
Sign up to set email alerts
|

NOD-like receptor signaling and inflammasome-related pathways are highlighted in psoriatic epidermis

Abstract: Psoriatic skin differs distinctly from normal skin by its thickened epidermis. Most gene expression comparisons utilize full-thickness biopsies, with substantial amount of dermis. We assayed the transcriptomes of normal, lesional, and non-lesional psoriatic epidermis, sampled as split-thickness skin grafts, with 5′-end RNA sequencing. We found that psoriatic epidermis contains more mRNA per total RNA than controls, and took this into account in the bioinformatic analysis. The approach highlighted innate immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 48 publications
5
75
0
Order By: Relevance
“…(12,13) Card6 also shares structural features with the interferon-inducible guanosine triphosphatase (GTPase) family and can be induced by interferon in bone marrow-derived macrophages, B cells, T cells, and splenocytes. (14) Other studies also implicate Card6 involvement in immune diseases and cancers, including psoriasis (15) and gastric, colorectal, and esophageal cancers. (16) Unexpectedly, Card6-deficient mice do not exhibit any abnormalities in the innate immune response.…”
Section: And Yi-da Tangmentioning
confidence: 99%
“…(12,13) Card6 also shares structural features with the interferon-inducible guanosine triphosphatase (GTPase) family and can be induced by interferon in bone marrow-derived macrophages, B cells, T cells, and splenocytes. (14) Other studies also implicate Card6 involvement in immune diseases and cancers, including psoriasis (15) and gastric, colorectal, and esophageal cancers. (16) Unexpectedly, Card6-deficient mice do not exhibit any abnormalities in the innate immune response.…”
Section: And Yi-da Tangmentioning
confidence: 99%
“…Genome-wide association studies suggest a link between NLRP10 and allergic and inflammatory pathways in atopic dermatitis, food allergies, and contact hypersensitivity. Most recently, NLRP10 was found upregulated in psoriasis, which is an immune-mediated genetic disease manifested in the skin and joints and shown to contribute to delayed-type hypersensitivity response in a mouse model of atopic dermatitis (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…2a). Several reports demonstrated that the expression of inflammasome components including AIM2, NOD2 and PYCARD was upregulated in psoriasis; 5,6 however, high expression of the NLRC4 gene in psoriatic lesions has never been reported. Our LC-MS/MS analysis did not detect the previously reported inflammasomes related to psoriasis probably because our sampling and analysis methods differed from those used in the previous studies.…”
Section: Discussionmentioning
confidence: 99%